2015
DOI: 10.1016/j.ajhg.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Alanyl-tRNA Synthetase Mutations Cause an Autosomal-Recessive Early-Onset Epileptic Encephalopathy with Persistent Myelination Defect

Abstract: Mutations in genes encoding aminoacyl-tRNA synthetases are known to cause leukodystrophies and genetic leukoencephalopathies-heritable disorders that result in white matter abnormalities in the central nervous system. Here we report three individuals (two siblings and an unrelated individual) with severe infantile epileptic encephalopathy, clubfoot, absent deep tendon reflexes, extrapyramidal symptoms, and persistently deficient myelination on MRI. Analysis by whole exome sequencing identified mutations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 25 publications
3
81
2
Order By: Relevance
“…Nine of the twenty-five cases had mutations in genes associated with disorders classically defined as leukodystrophies 3 (Table 1 & Supplemental Table S1): two patients were identified with TUBB4A (MIM:602662) related hypomyelination (Hypomyelination with atrophy of the basal ganglia and cerebellum [MIM:612438]) 24 ; two patients were identified with early onset Vanishing White Matter Disease (MIM:603896) (genotype EIF2B2 [MIM:606454] and EIF2B5 [MIM:603945]) 25, 26 ; three families were identified with t-RNA synthetase disorders ( AARS [MIM:601065] and DARS [MIM:603084]) 2729 ; and two families identified with a POLR3-related disorder ( POLR3B [MIM:614366] and POLR1C [MIM:610060]) (Table 1, Supplemental Table S2 and Supplemental Case Reports). 30 The remaining individuals had mutations in genes associated with genetic leukoencephalopathies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the twenty-five cases had mutations in genes associated with disorders classically defined as leukodystrophies 3 (Table 1 & Supplemental Table S1): two patients were identified with TUBB4A (MIM:602662) related hypomyelination (Hypomyelination with atrophy of the basal ganglia and cerebellum [MIM:612438]) 24 ; two patients were identified with early onset Vanishing White Matter Disease (MIM:603896) (genotype EIF2B2 [MIM:606454] and EIF2B5 [MIM:603945]) 25, 26 ; three families were identified with t-RNA synthetase disorders ( AARS [MIM:601065] and DARS [MIM:603084]) 2729 ; and two families identified with a POLR3-related disorder ( POLR3B [MIM:614366] and POLR1C [MIM:610060]) (Table 1, Supplemental Table S2 and Supplemental Case Reports). 30 The remaining individuals had mutations in genes associated with genetic leukoencephalopathies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other CMT-linked mutations have been reported to cause a loss of charging activity, suggesting that haploinsufficiency of the enzyme may be a possible contributing factor (Griffin et al, 2014; McLaughlin et al, 2012). Supporting this hypothesis, recessive mutations in synthetases have been linked to neurodegenerative disease, as well as many multisystem disorders involving a wider range of tissues, and many of these mutations have been found to reduce aminoacylation activity in vitro (Kodera et al, 2015; McLaughlin et al, 2010; van Meel et al, 2013; Meyer-Schuman and Antonellis, 2017; Nakayama et al, 2017; Puffenberger et al, 2012; Simons et al, 2015; Taft et al, 2013; Wolf et al, 2014; Zhang et al, 2014a). Impaired synthetase function may reduce the amount of charged tRNA available for translation elongation, with a possible increase in the levels of uncharged tRNA.…”
Section: Defects In Aminoacyl Trna Synthetase Function In Neurodegenementioning
confidence: 98%
“…Steady-state kinetics are calculated by fitting the initial rate of aminoacylation as a function of tRNA concentration (or the concentration of another substrate) to the Michaelis–Menten equation [43]. Aminoacylation assays have been used to demonstrate a loss-of-function effect on tRNA charging for mutations in 15 genes implicated in recessive disease ( AARS , CARS2 , DARS2 , FARS2 , IARS , KARS , LARS2 , MARS , MARS2 , QARS , RARS2 , SARS2 , TARS2 , VARS2 , and YARS2 ) [4,4459]. Interestingly, aminoacylation assays have also revealed a loss-of-function effect of GARS , YARS , and AARS mutations that cause dominant peripheral neuropathy (Table 2); HARS mutations associated with dominant CMT disease have not been tested.…”
Section: Functional Studies To Predict the Pathogenicity Of Ars Variantsmentioning
confidence: 99%
“…Yeast complementation assays have been used to demonstrate a loss-of-function effect on ARS function for mutations in eight genes implicated in recessive diseases ( AARS , AARS2 , HARS2 , IARS , KARS , LARS2 , MARS , VARS2 ) [6,44,47,48,52,57,63,64]. Similar to aminoacylation assays, in vivo studies in yeast have revealed a loss-of-function effect for GARS , YARS , AARS , and HARS mutations that cause dominant CMT disease (Table 2).…”
Section: Functional Studies To Predict the Pathogenicity Of Ars Variantsmentioning
confidence: 99%